Scientific and Pedagogical Projections of the Transformation of University Education - A. V. Kiryakova; N. A. Kargapoltseva; I. D. Belonovskaya (Moscow Polytechnic University, 2020)
University education has entered the stage of transformation; therefore, a scientific understanding of the future development paths is required. The purpose of the article is to present the experience of the scientific and pedagogical school of the university in studying the new challenges of society. Transformation of university education relates to such spheres as subjectivity and competence, student's personality self-determination, the model of interaction between subjects of university education, digital personality socialization in university's open educational space. The specificity and methodological basis of the study is the axiology of educational innovation. The scientific and pedagogical school fosters the processes of polytechnic university transformation into a multidisciplinary university in the conditions of humanization of engineering education. The article reveals the resources of the scientific and pedagogical activity of the humanitarian section of the university - the research activities of the team of pedagogical departments and the Dissertation Council, the implementation of grant projects and experimental sites of various levels.